2017
DOI: 10.1155/2017/5981217
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Colonography May Predict the Need for Bowel Resection in Colorectal Endometriosis

Abstract: Purpose To define if MRI findings in patients with deep pelvic endometriosis (DPE) may be predictive for the need of bowel resection. Material and Methods A retrospective survey of 196 pelvic MRIs of women who received laparoscopic procedures for DPE was carried out. A pelvic MRI was performed in all patients: it consisted in T2w-TSE sequences in axial, sagittal, and coronal planes and T1w and THRIVE sequences in the axial plane; the exam was completed by MR-Colonography. Intestinal lesions were measured in sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Regarding MRI, our study completes the recent findings concerning MRI measures of stenosis and long axis to predict the need for bowel resection In this study, a nodule’s short axis of 11 mm or more was a predictor for bowel resection with a sensitivity and a specificity of 93% and 99% respectively. Similarly, a bowel stenosis of 30% or more experienced a sensitivity of 95% and a specificity of 99% in predicting the need for a bowel resection[9]. Nevertheless, MRI colonography was a required parameter of this study, and this technique is only available in a limited number of centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding MRI, our study completes the recent findings concerning MRI measures of stenosis and long axis to predict the need for bowel resection In this study, a nodule’s short axis of 11 mm or more was a predictor for bowel resection with a sensitivity and a specificity of 93% and 99% respectively. Similarly, a bowel stenosis of 30% or more experienced a sensitivity of 95% and a specificity of 99% in predicting the need for a bowel resection[9]. Nevertheless, MRI colonography was a required parameter of this study, and this technique is only available in a limited number of centers.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that a pre-operative MRI-colonography might predict the need for bowel resection in recto-sigmoid endometriosis[9]. However, it has previously been demonstrated that RS-EUS exhibits better sensitivity and negative predictive value than MRI in the diagnosis of rectosigmoid endometriosis[10].…”
Section: Introductionmentioning
confidence: 99%
“…Colonic endometriosis is not a rare condition. It affects 37% of women with severe endometriosis [ 13 ], and its correct diagnosis is essential for the proper planning of treatment [ 15 , 48 , 50 , 51 ]. Recently, the ultrasound detection rate of endometriosis foci of the bowels has increased, exhibiting both high sensitivity and specificity [ 46 , 52 ].…”
Section: Sonographic Differential Diagnosismentioning
confidence: 99%
“…A systematic sonographic approach as defined by International Deep Endometriosis Analysis (IDEA) consensus was shown to improve detection rates of pelvic lesions [ 24 ]. MRI is also considered a highly accurate imaging modality in the evaluation of DIE, particularly when involvement of the rectum, ureters and nerve roots is suspected; these areas are highly important for both the patient and the surgeon and may be poorly visualized even with laparoscopy [ 25 , 26 ]. MRI is also increasingly used to assess the anatomic response to medical or surgical treatment and to differentiate endometriosis from adenomyosis; the latter is a specific and heterogeneous disease contributing, independently of endometriosis to symptoms, defined as the invasion of endometrial tissue into the myometrium occurring in different forms (diffuse, focal, cystic or superficial).…”
Section: Introductionmentioning
confidence: 99%